2013
DOI: 10.1523/jneurosci.4655-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Brain Activity Predicts Learning Ability of Foreign Sounds

Abstract: Can learning capacity of the human brain be predicted from initial spontaneous functional connectivity (FC) between brain areas involved in a task? We combined task-related functional magnetic resonance imaging (fMRI) and resting-state fMRI (rs-fMRI) before and after training with a Hindi dental-retroflex nonnative contrast. Previous fMRI results were replicated, demonstrating that this learning recruited the left insula/frontal operculum and the left superior parietal lobe, among other areas of the brain. Cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 50 publications
4
75
0
Order By: Relevance
“…These changes in rs-FC may reflect intrinsic and stable modifications related to vocabulary learning. This result agrees with previous studies showing that training in specific functions increased FC between local and distant brain areas involved in learning a new task (Lewis et al 2009;Baldassarre et al 2012;Ventura-Campos et al 2013). Therefore spontaneous activity patterns in the rs-fMRI may reflect a priori biases and the individual's propensities as a result of experience (Harmelech and Malach 2013).…”
Section: -Relationship Between Auditory and Motor Regions At Restsupporting
confidence: 92%
See 1 more Smart Citation
“…These changes in rs-FC may reflect intrinsic and stable modifications related to vocabulary learning. This result agrees with previous studies showing that training in specific functions increased FC between local and distant brain areas involved in learning a new task (Lewis et al 2009;Baldassarre et al 2012;Ventura-Campos et al 2013). Therefore spontaneous activity patterns in the rs-fMRI may reflect a priori biases and the individual's propensities as a result of experience (Harmelech and Malach 2013).…”
Section: -Relationship Between Auditory and Motor Regions At Restsupporting
confidence: 92%
“…Previous studies have shown that the intensity of correlations within and between brain areas at rest has behavioral significance (Harmelech and Malach 2013;Guerra-Carrillo et al 2014;Finn et al 2015), and that the resting-state activity may reflect the repeated history of co-activation within or between brain regions, which may in turn be a predictor of individual differences while performing perceptual, intelligence, and memory tasks (Lewis et al 2009;Baldassarre et al 2012;Cole et al 2012;Ventura-Campos et al 2013;Bueichekú et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We also plan to investigate and identify pretraining conditions that are predictive of training‐related changes in cortical thickness and rsFC of the individuals with TBI, and are linked to training outcomes (Arnemann et al., 2015; Ventura‐Campos et al., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…These changes in rs-FC may reflect intrinsic and stable modifications related to vocabulary learning. This result agrees with previous studies showing that training in specific functions increased FC between local and distant brain areas involved in learning a new task (Baldassarre et al, 2012;Lewis et al, 2009;Ventura-Campos et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, these results were associated with other changes in the brain showing the involvement of the dorsal pathway: the contrast between trained pseudowords > untrained words activated the inferior parietal lobe, the premotor cortex, and the cerebellum. The inferior parietal lobe is a key area in successful second language learning, as demonstrated in different anatomic and functional studies (Barbeau et al, 2016;Golestani & Pallier, 2007;Grogan et al, 2012;Mechelli, Crinion, et al, 2004;Ventura-Campos et al, 2013). The premotor cortex and the cerebellum are relevant in articulating learned pseudowords (Price 2012).…”
Section: Discussionmentioning
confidence: 99%